Tradisi Appabottingeng (Pesta Perkawinan) Masyarakat Suku Bugis Sulawesi Selatan: Perspektif Teori Perubahan Sosial Alvin Boskoff - Fatimah, Andi Fauziyah Hijrina; Inayah, Faidhul; Suyudi, Muhammad; Hasbi, Hasbi; Rasul, Rasul (Fakultas Ilmu Budaya, Universitas Jambi, 2024)
The Bugis ethnic group in South Sulawesi is known for various traditional customs, one of which is the traditional wedding ceremony known in Bugis language as